Vpliv skladnosti zaznane podobe znamke in porabnika na identifikacijo porabnika s trajnostnimi modnimi znamkami - Grubiša, Katja (Akademija MM, 2023)
This paper aims to provide insight into the antecedents and consequences of consumer-brand identification with sustainable fashion brands. Even though consumer-brand identification influences long-term relationships that can occur between consumers and brands and is therefore of vital importance in the sustainable fashion industry, this phenomenon remains insufficiently researched. The results of our quantitative study confirm that consumer-brand identification is an important strategic objective for sustainable fashion brands. Consumers who identify more strongly with a sustainable brand are more loyal to it, more willing to spread a positive voice about it, and more likely to choose the brand at their next purchase opportunity. The study also examines how consumer-brand identification can be achieved; it shows that identification with a sustainable fashion brand is significantly influenced by the congruence of the brand’s and consumer’s individual sustainable values and by the congruence of the consumer’s and brand’s fashion style. Additionally, consumer-brand identification is recognised as a mediator of consumer-brand congruity with further behavioral consequences. As such, the paper provides an insight into how important it is for sustainable fashion brands to become symbols through which consumers can express their identities in order to gain long-term support and overcome unsustainable overproduction and consumption in the fashion industry.
Keywords: Blagovne znamke; govorice; identifikacija porabnika; Oblačilna industrija; skladnost jaza; Trajnost (ekologija); trajnostna moda; zvestoba